Automotive and Construction Equipment for Arctic Use: Heating and Cold Starting - Diemand, Deborah (1991)
Low-temperature problems with automotive vehicles and equipment begin to appear at about 0 C. Lubricants thicken, batteries lose power, and water in the fuel, oil or other fluids begins to cause problems. Diesel engines that have not been winterized become difficult to start, and they may not start at all at temperatures below -10C. Gasoline engines start more reliably in the cold, but they suffer the same problems with regard to lubricants and batteries. The solution to these problems is heat. The amount of heat required and the means of applying it cannot be determined simply, as this will depend on the ambient temperature, wind speed, engine size and type, and degree of winterization of the engine. There are commercially available heaters for the following vehicle components: (1) engine block; (2) oil pan; (3) batteries; (4) fuel tanks, lines and filters; (5) transmission, differentials and transfer cases; (6) air intake; (7) combustion chamber; (8) engine compartment air; and (9) personnel and cargo compartments. Wind speed has a considerable effect on the amount of heat required to raise the temperature of a cold-soaked engine to a level at which it will start, and its effect on the cooling rate of a piece of equipment both during operation and after shutdown is significant. Heat loss experienced by a warm object in cold air varies with wind speeds. Some types of heaters used for warming cold engines are electric heaters and fuel fired heaters.